2020
DOI: 10.1002/hed.26361
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in patients with isolated regional recurrence after primary radiotherapy for head and neck cancer

Abstract: Background: Isolated regional recurrences following head-neck squamous-cell carcinomas (HNSCC) are often accessible for curatively intended salvage treatment. Factors prognostic for outcome were investigated in a large cohort of HNSCC patients. Methods: In total, 1811 patients receiving curatively intended radiotherapy from 2007 to 2017 were reviewed and isolated cervical nodal recurrences were identified. Factors associated with survival and second recurrence were investigated using univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In fact, the majority of studies on regional disease control reported heterogeneous data. In addition, these studies are mainly focused on the early‐stage oral squamous cell carcinoma, 44,45 or to the setting of planned neck dissection after primary RT 46,47 . Although the regional recurrence could not be always considered a direct consequence of occult node metastasis at the time of diagnosis, it would be interesting to know if a comparable rate of occult regional disease really exists to better understand the potential role of END.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the majority of studies on regional disease control reported heterogeneous data. In addition, these studies are mainly focused on the early‐stage oral squamous cell carcinoma, 44,45 or to the setting of planned neck dissection after primary RT 46,47 . Although the regional recurrence could not be always considered a direct consequence of occult node metastasis at the time of diagnosis, it would be interesting to know if a comparable rate of occult regional disease really exists to better understand the potential role of END.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these studies are mainly focused on the early-stage oral squamous cell carcinoma, 44,45 or to the setting of planned neck dissection after primary RT. 46,47 Although the regional recurrence could not be always considered a direct consequence of occult node metastasis at the time of diagnosis, it would be interesting to know if a comparable rate of occult regional disease really exists to better understand the potential role of END. Unfortunately, the time to regional relapse after surgery could not be extracted from included studies, and further data are needed to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, 18F‐fluoro‐deoxy‐ d ‐glucose (FDG) positron emission tomography (PET)/CT (FDG‐PET/CT) emerged as an alternative for the initial staging of sinonasal tumors, providing information on both metabolic activity and local extent of the primary tumor and on the presence of regional and distant metastases (DM). While various studies have investigated the diagnostic accuracy of FDG‐PET/CT in the staging and re‐staging of squamous cell carcinoma (SCC) of the upper aero‐digestive tract, only a few studies addressed its use for the initial staging of sinonasal tumors 9‐13 . Ozturk et al demonstrated that pretreatment diffusion‐weighted MRI in combination with FDG‐PET/CT parameters may serve as surrogate marker for the prognosis of sinonasal malignancies 14 .…”
Section: Introductionmentioning
confidence: 99%
“…While various studies have investigated the diagnostic accuracy of FDG-PET/CT in the staging and re-staging of squamous cell carcinoma (SCC) of the upper aerodigestive tract, only a few studies addressed its use for the initial staging of sinonasal tumors. [9][10][11][12][13] Ozturk et al demonstrated that pretreatment diffusion-weighted MRI in combination with FDG-PET/CT parameters may serve as surrogate marker for the prognosis of sinonasal malignancies. 14 Ramakrishnan et al reported a sensitivity of FDG-PET/CT of 94% for the diagnosis of sinonasal primaries, and a comparably high yield of regional metastases (27%) and DM (6%) in a cohort of 51 patients.…”
Section: Introductionmentioning
confidence: 99%
“…IRRs of head and neck malignancies are quite unusual, representing only 5.2% of all relapses; nevertheless, IRRs are associated with better survival compared to single local, or concomitant locoregional recurrences, as well as the onset of distant metastases 23 …”
Section: Discussionmentioning
confidence: 99%